THE MUSLIM COMMUNITY OF KYRGYZSTAN IN 1991-2013: GROWING PAINS - MURZAKHALILOV, Kanatbek (CENTRAL ASIA AND THE CAUCASUS, 2014)
The author analyzes the current state of affairs in the Muslim community of Kyrgyzstan and its relations with the state.Emerging and developing amid never ending conflict, the community has inevitably become relatively radicalized (the faithful -are divided into jamaats) and, at times, destructive. The author offers his own cures for the old and new problems of relations between the state and the Muslim community, the resolution of which is absolutely indispensable for their future development